Chagas Disease in a Non-Endemic Setting: Clinical Profile, Treatment Outcomes, and Predictors of Cure in a 15-Year Cohort Study - Carlos Bea-Serrano; Ana Isabel de Gracia-León; Jara Llenas-García; Sara Vela-Bernal; Andreu Belmonte-Domingo; Carolina Pinto-Pla; Ana Ferrer-Ribera; María José Galindo; María Jesús Alcaraz; María Rosa Oltra Sempere (Tropical Medicine and Infectious Disease, 2025)
This retrospective cohort study aimed to assess clinical and epidemiological characteristics, treatment outcomes, and predictors of serological cure in patients with chronic Chagas disease in a non-endemic setting. All individuals aged ≥16 years with confirmed infection and evaluated at a tertiary hospital in Spain from 2008 to 2023 were included. Most of the 107 participants were women (78.5%) and Bolivian-born (99.1%). Digestive and cardiac involvement were identified in 32.7% and 17.8% of cases, respectively. Cardiac symptoms were significantly associated with the diagnostic findings of cardiac involvement (odds ratio [OR] 3.0, 95% confidence interval [CI] 1.1–8.2), whereas digestive symptoms did not correlate with imaging abnormalities (OR 0.7, 95% CI 0.3–1.6). Antiparasitic treatment, usually benznidazole, was initiated in 69% of patients and led to adverse events in 66.2%, with treatment discontinuation in 25.7%. Only 8.1% of treated patients achieved serological cure after a median 26 months, with obesity emerging as the only independent predictor (adjusted OR 31.0, 95% CI 3.7–261.2). Cardiac progression occurred in 9.3% of patients despite treatment. Although 59.8% were lost to follow-up, the cohort maintained a median follow-up of 27 months. These findings underscore the need for improved treatment strategies and sustained clinical monitoring in non-endemic settings.